Deserters of Cremnops desertor (Hymenoptera: Braconidae: Agathidinae): Delimiting species boundaries in the C. desertor species-complex. Issue 4 (3rd July 2016) - Tucker, Erika M.; Sharkey, Michael J
Abstract : The concept of the species Cremnops desertor (Linnaeus, 1758 ) and its complicated taxonomic history are discussed. A phylogenetic distance tree, based on COI data, is used to help delimit species. The recognition of C. alternans Enderlein, 1920 and C. malayensis Bhat, 1979 is proposed. Images, distribution maps, and suggestions for further research are included.